Forever young: SIRT3 a shield against mitochondrial meltdown, aging, and neurodegeneration - Kincaid, Brad; Bossy-Wetzel, Ella (Frontiers in Aging Neuroscience, 2013)
Caloric restriction, fasting, and exercise have long been recognized for their neuroprotective and lifespan-extending properties; however, the underlying mechanisms of these phenomena remain elusive. Such extraordinary benefits might be linked to the activation of sirtuins. In mammals, the sirtuin family has seven members (SIRT1-7), which diverge in tissue distribution, subcellular localization, enzymatic activity and targets. SIRT1, SIRT2, and SIRT3 have deacetylase activity. Their dependence on NAD+ directly links their activity to the metabolic status of the cell. High NAD+ levels convey neuroprotective effects, possibly via activation of sirtuin family members. Mitochondrial sirtuin 3 (SIRT3) has received much attention for its role in metabolism and aging. Specific small nucleotide polymorphisms (SNPs) in Sirt3 are linked to increased human lifespan. SIRT3 mediates the adaptation of increased energy demand during caloric restriction, fasting and exercise to increased production of energy equivalents. SIRT3 deacetylates and activates mitochondrial enzymes involved in fatty acid β-oxidation, amino acid metabolism, the electron transport chain, and antioxidant defenses. As a result, the mitochondrial energy metabolism increases. In addition, SIRT3 prevents apoptosis by lowering reactive oxygen species (ROS) and inhibiting components of the mitochondrial permeability transition pore. Mitochondrial deficits associated with aging and neurodegeneration might therefore be slowed or even prevented by SIRT3 activation. In addition, upregulating SIRT3 activity by dietary supplementation of sirtuin activating compounds might promote the beneficial effects of this enzyme. The goal of this review is to summarize emerging data supporting a neuroprotective action of SIRT3 against Alzheimer’s disease (AD), Huntington’s disease (HD), Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS).